An experimental investigation and optimisation of flat plate heat sink. (1st January 2012) - Manivannan, S.; Arumugam, R.; Prasanna Devi, S.; Sudharsan, N.M.; Paramasivam, S.
This study is focused on multiple response optimisation of a flat plate heat sink using grey relational analysis and Taguchi design of experiments. The responses considered are electromagnetic emitted radiation and thermal resistance of the heat sink. The emitted radiation and thermal resistance of the heat sink were obtained using Ansoft HFSS and Flotherm CFD simulation, respectively. The experimental investigations were carried for the validation of simulation results. The responses were found for the L27 (six factors, three levels) Taguchi-based design of experiments combinations. The ANOVA test was carried to test the significance of the design parameters towards the multi-objective optimisation. From the results of GRA, it is inferred that number of fins, width and base height are the most influencing parameters influencing the simultaneous minimisation of the responses studied.